Digital disinformation strategies of European climate change obstructionist think tanks - Moreno-Cabanillas, Andrea; Castillero-Ostio, Elizabet; Serna-Ortega, Álvaro (Frontiers in Communication, 2024)
This study explores how European think tanks with obstructive positions on climate policy use the social network X to advance their agendas. The aim is to understand their digital communication strategies, the issues they address, the use of hyperlinks, and the impact on interaction and online polarization. A mixed-methods analysis was conducted on tweets from twelve organizations known for opposing climate policies. Out of an initial 96,607 tweets, 803 relevant messages were selected to evaluate thematic content and interaction reach. The analysis identified five dominant thematic areas in the tweets: economic impacts of climate policy, ideological perspectives, questioning of official science, proposed technological solutions, and other messages. The higher levels of interaction were generated by messages with a political or ideological focus and those proposing technological solutions. In addition, most hyperlinks directed users to the think tanks' own websites rather than to external sources. European anti-climate change think tanks use social network X to promote their agendas through ideological and technical messages that generate high engagement.